Patrón de vocalización de Mimus longicaudatus en ámbito urbano, 2018 - Vásquez Cabrera, Roberto Carlos (2018)
The general objective of this work was to determine the vocalization patterns of Mimus longicaudatus TSCH., 1844 in urban areas. To achieve this goal, recordings were made in the hours from 07:00 to 10:00 and from 16:00 to 19:00. The initial sounds and songs were recorded according to the activity and behavior of the species, the maximum intensity (measured in decibels [dB], as an indication of the volume of the same) of the vocalizations was also recorded. Five points were considered along a 100m transect, each point separated from the other by 20 m. At each point the observer made recordings of 3 to 5 minutes. The vocalizations were recorded and processed with the Audacity Program and Raven Lite 2.0 (free software) for the analysis of the intensity, frequency and variation of the audios, as well as the elaboration of sonograms. The results showed that the frequency of the songs emitted varies from 0 to 18 kHz. It is concluded that there is a close relationship between the vocalization pattern and the activities performed by the individuals of Mimus longicaudatus TSCH., 1844 "chisco".